Origins and development of recollection perspectives from psychology and neuroscience - Ghetti, Simona; Bauer, Patricia J. (New York ; Oxford : Oxford University Press, 2012)
The ability to remember unique, personal events is at the core of what we consider to be 'memory.' Contributors to this volume use state-of-the-art theories and methods to address questions of how the vivid experience of reinstatement of our past emerges, and how recollection contributes to our life histories.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Recollection (Psychology); Memory